Pengaruh Penggunaan Multimedia Interaktif Berbasis Media Video Terhadap Hasil Belajar Fisika Pada Siswa SMP Negeri 1 Lemboraya - Fika Italiani Darae; Amiruddin Hatibe (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2023)
This study aims to determine the effect of the use of interactive multimedia based on video media on physics learning outcomes for students of SMP Negeri 1 Lemboraya. The research method used is a quasi-experimental method that seeks to reveal a causal relationship by involving the control group and the experimental group, taking into account the difficulty of controlling all the variables that have the variables studied. The test results on this hypothesis test obtained data analysis results show  tcount> ttable or 5,81> 1,68. This means, the value of tcount is outside the reception area H0 . Thus, H0 is rejected and H1 is accepted. Based on these data it can be concluded that there is an effect of learning outcomes between the experimental class using interactive multimedia based on video media on student learning outcomes of physics, with the control class using conventional learning models. The data from the results of this study can be concluded that student learning outcomes in the experimental class are better than the control class.